An Approach to Ranking the Sources of Information Dissemination in Social Networks - Lidia Vitkova; Igor Kotenko; Andrey Chechulin (Information, 2021)
The problem of countering the spread of destructive content in social networks is currently relevant for most countries of the world. Basically, automatic monitoring systems are used to detect the sources of the spread of malicious information, and automated systems, operators, and counteraction scenarios are used to counteract it. The paper suggests an approach to ranking the sources of the distribution of messages with destructive content. In the process of ranking objects by priority, the number of messages created by the source and the integral indicator of the involvement of its audience are considered. The approach realizes the identification of the most popular and active sources of dissemination of destructive content. The approach does not require the analysis of graphs of relationships and provides an increase in the efficiency of the operator. The proposed solution is applicable both to brand reputation monitoring systems and for countering cyberbullying and the dissemination of destructive information in social networks.